Exploring knowledge, attitude, and practices in relation to epilepsy among undergraduates for effective health promotion: Initial evaluation - Meena Kolar Sridara Murthy; Lakshmana Govindappa; P Marimuthu; Madhuporna Dasgupta (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: The condition of epilepsy has a considerable effect on a person's social and personal life. Currently, a knowledge gap exists regarding the knowledge, attitude, and perception towards epilepsy among graduate students. The objectives of the study were to initially explore the knowledge, attitude, practices and to examine their inter-relationship among graduate students. MATERIALS AND METHODS: A total of 300 3rd year Bachelor of Science graduate students from colleges near Hombegowda nagar, Bangalore, Karnataka were included from three colleges. To achieve the objective mentioned, an instrument was framed and approved by specialists in the field. RESULTS: About 26% believed that epilepsy is a mental illness, 64% reported that it is not a disease of the brain, 96% believed it to be a hereditary disease. Attitude shows that 29%, 33%, and 49% believed that Epilepsy can disturb anybody's normal life, education, and occupation, respectively. About 31% reported that if they see a person with epileptic attack they ran away. Knowledge score have significantly (P < 0.001) positive correlation of r = 0.810 and r = 0.794 with both attitude and practice, respectively. Attitude and practice also have significantly (P < 0.001) positive correlation (0.856) with practice. This clearly shows that if knowledge increases, persons will have positive attitude and good practices whereas less knowledge leads to faulty attitude and practices. CONCLUSIONS: There is a need to include health education programs for school children and college students irrespective of streams, as it is crucial to bring an alteration in the presently observed perspective, behavior, and practice.